Eektivitas Metode Iqro dalam PembelajaranAl-Qur’an (Studi Kasus TPQ Al Barokah) - Inayah, Nikmatul; Alawiyah, Tuti; Sulaeman, Sulaeman; Miskiyah, Nafahatul; Umam , Nadziful (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The Qur'an is the main source of law and guidance for Muslims, so the ability to read the Qur'an properly and correctly is a basic competency that must be acquired from an early age. This study aims to analyse the effectiveness of the Iqro method in teaching Qur'an reading at TPQ Al Barokah and to identify the supporting and inhibiting factors in its implementation. The research used a qualitative approach with a case study type. Data collection was carried out through observation, in-depth interviews, and documentation involving 5 teachers, 54 students, and 2 TPQ administrators. Data analysis was carried out interactively through the stages of data reduction, data presentation, and conclusion drawing, accompanied by triangulation of techniques and sources to ensure data validity. The results showed that the Iqro method was effective in improving students' ability to read the Qur'an, as seen from the development of their abilities, ranging from recognition of Hijaiyah letters to fluency in reading according to the rules of tajwid. The main supporting factors included intensive guidance from teachers, student motivation to learn, and parental support. Meanwhile, the inhibiting factors include differences in the students' abilities, limited learning facilities, and relatively limited learning time. Overall, the application of the Iqro method is not only effective in improving the students' ability to read the Qur'an, but also contributes to building their confidence, discipline, and love for the Qur'an